Public Support for Smoke-Free Section 8 Public Housing. (August 2019) - McMillen, Robert C.; Winickoff, Jonathan P.; Gottlieb, Mark A.; Tanski, Susanne; Wilson, Karen; Klein, Jonathan D.
The U.S. Department of Housing and Urban Development (HUD) recently issued rules requiring that federally funded authorities administering public housing must have smoke-free policies. Importantly, this requirement does not extend to Section 8 housing. Under the Section 8 program, public housing vouchers provide subsidies for private rental housing to low-income residents. This study examines support for smoke-free policy options in Section 8 housing. Using a nationally representative survey of adults, we asked 3, 070 respondents to agree or disagree with two potential policies. The majority (71%) supported prohibiting indoor smoking everywhere inside buildings that have Section 8 housing units. Alternatively, respondents were less supportive (38%) of a policy to prohibit smoking only inside units with Section 8 subsidies, and allowing smoking in nonsubsidized units. Prohibiting smoking in all units in multiunit housing (MUH) buildings would help protect the health of both the 2.2 million households who receive Section 8 subsidies and their neighbors.